Steel designers' handbook - Gorenc, B. (Branko); Tinyou, R. (Ronald); Syam, A. (Arun) (Sydney, NSW : UNSW Press, 2005)
The seventh edition of Steel Designers' Handbook text is fully revised and covers the extensive revision of the 'loading code', which is renamed as structural Design Actions Standard, General Principals. AS/ANZ 1170.0 and its companion parts, 1170.1 to 1170.3. The volume of revisions and new terminology necessitated the first three chapters to be substantially rewritten. This edition is based on AS 4100: 1998, which incorporates revisions to the original 1990 edition.
Contents; Preface; chapter 1 Introduction; chapter 2 Material & Design Requirements; chapter 3 Design Actions; chapter 4 Structural Analysis; chapter 5 Beams & Girders; chapter 6 Compression & Beam-Column Members; chapter 7 Tension Members; chapter 8 Connections; chapter 9 Plastic Design; chapter 10 Structural Framing; Appendix A Bibliography; Appendix B Elastic Design Method; Appendix C Design Aids; Notation; Index.
Includes bibliographical references (pages 322-331) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Steel, Structural; Building, Iron and steel; Civil Engineering; Civil & Environmental Engineering; Engineering & Applied Sciences; Acier de construction; Construction métallique.; structural steel; TECHNOLOGY & ENGINEERING -- Structural; Building, Iron and steel; Steel, Structural